Trends in using internet-based learning media for students during the COVID-19 pandemic - Muhammad Yus Firdaus; Mustofa Kamil; Purnomo Purnomo (Inovasi Kurikulum, 2024)
The COVID-19 pandemic has led to a profound transformation in the global education system, forcing a sudden shift from face-to-face teaching to online learning. This study aims to understand how students have utilized technology for online learning during the pandemic, focusing on using the internet and smartphones and evaluating the effectiveness of various applications and platforms such as WhatsApp, Zoom, and Learning Management Systems (LMS). A descriptive quantitative research method was employed with a survey technique involving 220 students from Universitas Islam Syekh-Yusuf (UNIS) to gather data on their technology use activities. The findings indicate that UNIS students predominantly use the internet for learning and information-seeking, while smartphones are more frequently used for communication and entertainment. WhatsApp and Zoom are the most commonly used applications for online learning, reflecting a preference for familiar and easily accessible platforms. The study highlights the need for improved digital skills and technology access to support more effective learning. Recommendations include developing technology training for educators, providing better student resources, and integrating online learning models into long-term educational strategies to enhance education quality and flexibility.   Abstrak Pandemi COVID-19 telah mengakibatkan transformasi mendalam dalam sistem pendidikan global, memaksa pergeseran dari metode tatap muka ke pembelajaran daring secara mendadak. Penelitian ini bertujuan untuk memahami penggunaan teknologi oleh mahasiswa dalam konteks pembelajaran daring selama pandemi, dengan fokus pada pemanfaatan internet dan smartphone, serta efektivitas berbagai aplikasi dan platform seperti WhatsApp, Zoom, dan LMS. Metode penelitian kuantitatif deskriptif digunakan dengan teknik survei terhadap 220 mahasiswa Universitas Islam Syekh-Yusuf (UNIS) untuk mengumpulkan data mengenai aktivitas teknologi mereka. Hasil penelitian menunjukkan bahwa mahasiswa UNIS dominan menggunakan internet untuk belajar dan mencari informasi, sementara smartphone lebih sering digunakan untuk komunikasi dan hiburan. WhatsApp dan Zoom adalah aplikasi paling sering digunakan untuk pembelajaran daring, mencerminkan preferensi terhadap platform yang familiar dan mudah diakses. Temuan ini menyoroti perlunya peningkatan keterampilan digital dan akses teknologi untuk mendukung pembelajaran yang lebih efektif. Penelitian ini menyarankan pengembangan pelatihan teknologi untuk pengajar dan penyediaan sumber daya yang lebih baik bagi mahasiswa, serta integrasi model pembelajaran daring dalam strategi pendidikan jangka panjang untuk meningkatkan kualitas dan fleksibilitas pendidikan. Kata Kunci: COVID-19; pembelajaran jarak jauh; pembelajaran online